New cave-dwelling spiders of the family Nesticidae (Arachnida, Araneae) from China - Liu, Jie; Li, Shuqiang (Zootaxa, 2013)
Nine new species of the family Nesticidae, collected from caves in Guangxi, Guizhou, Henan and Yunnan Provinces of China, are diagnosed, described and illustrated: Nesticella apiculata n. sp., Nesticella arcuata n. sp., Nesticella falcata n. sp., Nesticella gracilenta n. sp., Nesticella semicircularis n. sp., Nesticella shanlinensis n. sp., Nesticella verticalis n. sp., Nesticus globosus n. sp. and Nesticus navicellatus n. sp. Nesticella mogera (Yaginuma, 1972), from Guizhou, is described and compared to the new species.